ISLAMICATE CIVILIZATION AND NATIONAL ISLAMS: ISLAM NUSANTARA, WEST JAVA AND SUNDANESE CULTURE - Woodward, Mark (Center for Research and Development of Religious Literature and Heritage, 2019)
Relationships between Islam and local cultures, post-coloniality, the construction of National Islams and nationalisms are extraordinarily complex. They pose complex academic, theological and political problems. This paper considers examples from the province of West Java in post-colonial Indonesia. It will be concerned with the ways in which elements of local West Javanese/Sundanese culture are rejected by Islamist nationalists but at the same time incorporated into a regional variant of the culture friendly Islam Nusantara formulated by Nahdlatul Ulama (NU) in 2015. See Chamami (2015) and Woodward (2018). It also suggests that what Philosopher of Science Karl Popper termed the ?situational logic? of Islam Nusantara is based on principles that have driven the construction of what Historian Marshal Hodgson (1974) termed Islamicate Civilizations since they emerged in the sixth century. Thorough consideration of these questions requires an overarching analytic and theoretical framework. Without one, we can produce disconnected, fragmentary analyses with limited practical applications. This paper is an attempt to establish such a framework. Building on Berger?s constructivist approach to the Sociology of Religion, it draws on seemingly divergent themes in the academic discourse about religion/society/state relationships in hope that the resulting synthesis will be of greater analytic utility and practical applicability than the sum of its parts. Empirically it focuses on West Java, Sundanese culture and emergence of alternative National Islams in contemporary Indonesia. It also makes comparative references to neighbouring countries, especially Malaysia. Theoretically, it is transdisciplinary, combining approaches from Cultural Anthropology, History, Political Science and Religious Studies. Given the current state of intra-Islamic political and religious discourse, it also necessarily focuses on debates between Sufi oriented ?traditionalists? and Salafi oriented ?modernists? that have been a major feature of colonial and post-colonial Muslim discourse for more than a century. It argues that alternative National Islams are shaped by a combination of theological debates and religion/state/society dynamics.